2021
DOI: 10.4103/jfmpc.jfmpc_1820_20
|View full text |Cite
|
Sign up to set email alerts
|

Daily self-regulation with biofeedback to improve stress and job satisfaction in a primary care clinic

Abstract: Background: Burnout in healthcare professions is higher than other careers. An undesirable work-life balance has resulted in declining job satisfaction among primary care physicians. Biofeedback devices teach self-regulation techniques, which reduce stress and increase resilience. Objectives: We assessed whether self-regulation with biofeedback is effective at decreasing stress and improving job satisfaction among primary care clinicians and nurses. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Relevant research on the influence of Kouzes and Posner's exemplary leadership styles, selfregulation, and job satisfaction on teacher performance has included; the influence of Kouzes and Posner's exemplary leadership that impacted job satisfaction has been exercised by Zufani et al (2017, 225-238); Salleh & Khalid (2018, 208-220) who found that Kouzes and Posner's exemplary leadership had a positive impact on teacher job satisfaction. On the effect of teacher self-regulation variables on job satisfaction, previous research has been conducted by Orlando et al (2021), which states that well-formed self-regulation will result in employee job satisfaction. On the influence of Kouzes and Posner's exemplary leadership variables on teacher performance, previous research has been conducted by Syawal (2021, 704); Abu-Tineh et al (2009, 283); Goewey (2012, 118) who states that Kouzes and Posner's exemplary leadership by school leaders will result in major changes in school progress manifested from teacher performance.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research on the influence of Kouzes and Posner's exemplary leadership styles, selfregulation, and job satisfaction on teacher performance has included; the influence of Kouzes and Posner's exemplary leadership that impacted job satisfaction has been exercised by Zufani et al (2017, 225-238); Salleh & Khalid (2018, 208-220) who found that Kouzes and Posner's exemplary leadership had a positive impact on teacher job satisfaction. On the effect of teacher self-regulation variables on job satisfaction, previous research has been conducted by Orlando et al (2021), which states that well-formed self-regulation will result in employee job satisfaction. On the influence of Kouzes and Posner's exemplary leadership variables on teacher performance, previous research has been conducted by Syawal (2021, 704); Abu-Tineh et al (2009, 283); Goewey (2012, 118) who states that Kouzes and Posner's exemplary leadership by school leaders will result in major changes in school progress manifested from teacher performance.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion-aware proactive and reactive technologies are another example of emerging digital media capabilities that use and process affective input to enhance user experience (Harley et al, 2017). Users can also leverage those affective capabilities to improve emotional control, awareness, and well-being (Orlando et al, 2021;. These new affective channels appear designed to improve convergence, rather than conveyance, and yet they are not designed to resemble faceto-face interaction.…”
Section: From Natural Media To Embodied Mediamentioning
confidence: 99%